Adaptive integral robust control and application to electromechanical servo systems. (March 2017) - Deng, Wenxiang; Yao, Jianyong
Abstract: This paper proposes a continuous adaptive integral robust control with robust integral of the sign of the error (RISE) feedback for a class of uncertain nonlinear systems, in which the RISE feedback gain is adapted online to ensure the robustness against disturbances without the prior bound knowledge of the additive disturbances. In addition, an adaptive compensation integrated with the proposed adaptive RISE feedback term is also constructed to further reduce design conservatism when the system also exists parametric uncertainties. Lyapunov analysis reveals the proposed controllers could guarantee the tracking errors are asymptotically converging to zero with continuous control efforts. To illustrate the high performance nature of the developed controllers, numerical simulations are provided. At the end, an application case of an actual electromechanical servo system driven by motor is also studied, with some specific design consideration, and comparative experimental results are obtained to verify the effectiveness of the proposed controllers. Highlights: A continuous robust feedback with adaptive compensation for uncertain nonlinear systems. Adaptive robust gain without the knowledge of the unmodeled disturbances. Asymptotic tracking property with the proposed continuous controller. Experimental verification for an electromechanical system.